Legal Position of Joint Property in Marriage Without a Pre-Nuptial Agreement - Heru Sunardi; Jamaludin Jamaludin; Adamu Abubakar Muhammad (Fiat Justisia: Jurnal Ilmu Hukum, 2026)
Marriage has legal consequences for the control and distribution of joint assets, particularly in the absence of a prenuptial agreement, which can create uncertainty and weaken the protection of personal property. This study examines the regulation of joint assets in prenuptial agreements under Law Number 16 of 2019 amending Law Number 1 of 1974 concerning Marriage and Presidential Instruction Number 1 of 1991 on the Compilation of Islamic Law (KHI), as well as the legal status of joint assets in marriages without such agreements. Using a normative legal research method with statutory and conceptual approaches, the study analyzes primary, secondary, and tertiary legal materials through literature review and qualitative description. Findings indicate that prenuptial agreements provide for the separation of assets and legal certainty, while marriages without agreements merge all assets into joint property, affirming equal rights between spouses but offering limited protection for personal property. The study highlights the strategic role of prenuptial agreements in safeguarding economic rights and ensuring legal certainty in marital property management.